(untitled) (PANGEEA, 2025)
Population trends in the Apuseni Mountains in view of sustainable development. The sustainable development has to ensure the balance between the socio-economic elements and the environmental elements in order to increase the welfare of the human society. Only the people (the human resources) can enhance the value of the natural resources. The Central Development Region, the Alba County and the Apuseni Mountains Region are affected by the fact that the miners lost their job. The unemployment caused a lot of negative demographic phenomena through the emigration of young people. The only people that left are old. The beautiful landscape can not be seen because the region of The Apuseni Mountains is very isolated. The development of society, has some opportunities, but the inhabitants must be informed about them in order to invest more in tourism, farming or education.